2015
DOI: 10.1080/15389588.2015.1052420
|View full text |Cite
|
Sign up to set email alerts
|

Seat belt use and fit among drivers aged 75 years and older in their own vehicles

Abstract: The results suggest that older drivers face challenges in achieving comfortable and correct seat belt fit. This may have a negative impact on crash protection. Belt fit problems appear to be associated with body shape, particularly high BMI and gender. There is a need for further investigation of comfort accessories; in the interim, older drivers and occupants should be encouraged to use features such as D-ring adjusters to improve sash belt fit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
15
0
3
Order By: Relevance
“…We recently examined seat belt‐wearing patterns and quality of fit among drivers aged 75 years and older in their own vehicles and found these occupants to experience problems achieving good seat belt fit. This appeared to be associated with some of the body shape changes associated with ageing . We also found that many of the older occupants report discomfort in seat belts.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…We recently examined seat belt‐wearing patterns and quality of fit among drivers aged 75 years and older in their own vehicles and found these occupants to experience problems achieving good seat belt fit. This appeared to be associated with some of the body shape changes associated with ageing . We also found that many of the older occupants report discomfort in seat belts.…”
Section: Introductionmentioning
confidence: 53%
“…We also found that many of the older occupants report discomfort in seat belts. This was associated with belt‐repositioning behaviours, including placing the belt under the arm or behind the back . Furthermore, occupants who were experiencing discomfort were also more likely to be using some sort of seat accessory, such as seat base cushions, seat back cushions and back supports (See Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…For older adults, changes in posture and fat distribution can lead to difficulties with belt fit. In a study by Fong et al (2016), the shoulder belt fit was judged optimal if the shoulder belt passed over the mid-portion of the shoulder. Lap belt fit was judged optimal if the belt was positioned below the anterior-superior iliac spines (ASIS) landmarks and in contact with the upper thigh (Reed et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This may result in the seat belt being perceived as uncomfortable when worn tightly, and efforts to minimize discomfort may lead to incorrect usage. People sometimes use accessories such as pillows to reduce discomfort Fong et al 2016) but still feel strapped in and protected in the event of a collision. Perceived safety is misleading due to a lack of understanding of how a protective system works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation